Penggunaan Strategi Pembelajaran Holistik Untuk Menumbuhkan Karakter Anak Usia Dini Pada Kelompok B Di Ra An Nisa Kedawung Tahun Ajaran 2014/2015 - Khoiriyah, Nur, Dr. Sabar Narimo, M.M., M.Pd, Dr. Sofyan Anif, M.Si (2015)
The problem of this research contents is about the low of children character. The purpose of this research is to grow up the children character by appliying the implementation of Holistic Learning Strategy in group B of RA An Nisa' Kedawung at Academic Year 2014/2015. The kind of this research is classroom action research with was conducted in three cycles. The subject of this research is group B with total children 22. The object research is the Holistic Learning Strategy. The research instrument is a character indicator, there are three character, there are independence, dicipline and responsibility with 12 item of opbservation. The collecting data is conducted by observasing, noting, interviewing and documenting. Based on the result of research is appear that the character grow up significanly. The first cycles for independance charakter is 43%, the second cycles is 57%, and the third cycles is 75%. And than the dicipline character for firs cycles is 50%, the second cycle is 61% an the third cycles is 78%. And the responsible character for the first character is 39%, and the second character is 54% , and the third character is 78%. From the observation can be see that the character can grow up by using Holistic Learning Strategy in learning process.